Analyzing Religious Conflicts On Social Media Based On The First Principle Of Pancasila - -, Kadek Yoga Artha Yudha; Maharani, Nikita; Muhammadong, Muhammadong (Journal of Digital Law and Policy, 2024)
The development of communication technology is accelerating. Whatever happens in Indonesia can easily be sent through the Internet network. Social media is a communication and marketing tool where people can share their thoughts, ideas and experiences with others. It is a form of electronic media that allows people to create content and share it with the public. Social media has many positive and negative effects on society. If people do not use social media wisely and it goes viral, it can lead to unwanted conflicts. One of them is the religious conflict that is currently widespread, thus becoming a real threat to the Indonesian nation. The threat is not only in the real world, but also in cyberspace. Many people are indirectly uploading what is on their minds to social media, which can cause others to be offended. This is the beginning of religious conflict on social media. This is where the role of the government as well as the community is to understand that we live together in differences of ethnicity, religion and language. The role of the government can also be to firmly control the application of press laws and journalistic ethics. In addition, the role of the community is also important, namely by not being easily provoked by media coverage that is not balanced and seems to favor one particular group.